2015
DOI: 10.1039/c4tb01899k
|View full text |Cite
|
Sign up to set email alerts
|

A novel rGR–TiO2–ZrO2 composite nanosheet for capturing phosphopeptides from biosamples

Abstract: A novel rGR–TiO2–ZrO2 composite nanosheet was synthesized and applied to selectively capture phosphopeptides from complex biosamples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…[11][12][13][14] Recently, it has been proved that guanidyl groups could be regarded as a better functionalized group to improve the binding of the phosphate groups and prevent the binding of other peptides. [15][16][17] Inspired by this, the guanidyl groups are modied on the TiO 2 , which will offer higher capacity of phosphopeptides binding due to the interaction between the phosphate groups and guanidyl groups. 18,19 The aim of this work is to design and synthesize a novel MOAC material with guanidyl-functionalized TiO 2 nanoparticles (GF-TiO 2 ) anchored on the surface of graphene oxide (GO) platform (denoted as GF-TiO 2 -GO) for selective enrichment of phosphopeptides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] Recently, it has been proved that guanidyl groups could be regarded as a better functionalized group to improve the binding of the phosphate groups and prevent the binding of other peptides. [15][16][17] Inspired by this, the guanidyl groups are modied on the TiO 2 , which will offer higher capacity of phosphopeptides binding due to the interaction between the phosphate groups and guanidyl groups. 18,19 The aim of this work is to design and synthesize a novel MOAC material with guanidyl-functionalized TiO 2 nanoparticles (GF-TiO 2 ) anchored on the surface of graphene oxide (GO) platform (denoted as GF-TiO 2 -GO) for selective enrichment of phosphopeptides.…”
Section: Introductionmentioning
confidence: 99%
“… 11–14 Recently, it has been proved that guanidyl groups could be regarded as a better functionalized group to improve the binding of the phosphate groups and prevent the binding of other peptides. 15–17 Inspired by this, the guanidyl groups are modified on the TiO 2 , which will offer higher capacity of phosphopeptides binding due to the interaction between the phosphate groups and guanidyl groups. 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…and they all show different preference for different phosphopeptides. According to the reports in the literature, APs integrating binary metal oxides (BMOs) can significantly improve the enrichment efficiency ,which triggered our interest to develop new BMOAPs for highly selective enrichment of phosphopeptides. Among all the metal oxides that are widely used in phosphoproteomics research, TiO 2 and ZrO 2 demonstrate outstanding enrichment ability toward phosphopeptides.…”
Section: Methodsmentioning
confidence: 99%
“…1436 phosphorylated sites corresponding to 622 phosphopeptides (163 mono‐ and 459 multiphosphopeptides) were identified from the identical mouse brain extracts. Moreover, Huang et al integrated TiO 2 and ZrO 2 via sol–gel and hydrothermal treatment method, and identified 1980 and 577 phosphopeptides from the extracts of mouse brain and mouse liver, respectively . Liu et al integrated Ti and Zr into MOFs to fabricate binary MOFs with Zr–O and Ti–O units (Figure B), and identified 44 phosphopeptides (34 mono‐ and 10 multiphosphopeptides) from 1 µL of human saliva .…”
Section: Nanomaterials In Phosphoproteomicsmentioning
confidence: 99%